Depressive Symptoms and Cardiovascular Health by the American Heart Association’s Definition in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study - Kronish, Ian M. (Public Library of Science, 2012)
BACKGROUND: Depressive symptoms are associated with increased incident and recurrent cardiovascular events. In 2010, the American Heart Association published the Life’s Simple 7, a metric for assessing cardiovascular health as measured by 4 health behaviors (smoking, physical activity, body mass index, diet) and 3 biological measures (cholesterol, blood pressure, glucose). The association between depressive symptoms and the Life’s Simple 7 has not yet been explored. METHODS: Data from 20,093 participants ≥45 years of age who enrolled in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study between 2003 and 2007 and who had complete data available on Life’s Simple 7 components were used for these analyses. The prevalence of ideal, intermediate, and poor health on each Life’s Simple 7 component and total Life’s Simple 7 scores were compared between participants with and without depressive symptoms. Depressive symptoms were measured using the 4-item Centers for Epidemiologic Studies of Depression scale. RESULTS: Participants with depressive symptoms were more likely to have poor levels on each of the Life’s Simple 7 components other than cholesterol [adjusted prevalence ratios (95% CI): smoking 1.41 (1.29–1.55); physical activity 1.38 (1.31–1.46); body mass index 1.09 (1.04–1.15); diet 1.08 (1.06–1.10); blood pressure 1.11 (1.02–1.21); glucose 1.24 (1.09–1.41)]. There was a graded association between increasing depressive symptoms and lower total Life’s Simple 7 score. CONCLUSION: Depressive symptoms are associated with worse cardiovascular health on the overall Life’s Simple 7 and on individual components representing both health behaviors and biological factors.